Update on the Genetic Polymorphisms of Drug-Metabolizing Enzymes in Antiepileptic Drug Therapy - Junji Saruwatari; Takateru Ishitsu; Kazuko Nakagawa (MDPI AG, 2010)
Genetic polymorphisms in the genes that encode drug-metabolizing enzymes are implicated in the inter-individual variability in the pharmacokinetics and pharmaco-dynamics of antiepileptic drugs (AEDs). However, the clinical impact of these polymorphisms on AED therapy still remains controversial. The defective alleles of cytochrome P450 (CYP) 2C9 and/or CYP2C19 could affect not only the pharmacokinetics, but also the pharmacodynamics of phenytoin therapy. CYP2C19 deficient genotypes were associated with the higher serum concentration of an active metabolite of clobazam, N-desmethylclobazam, and with the higher clinical efficacy of clobazam therapy than the other CYP2C19 genotypes. The defective alleles of CYP2C9 and/or CYP2C19 were also found to have clinically significant effects on the inter-individual variabilities in the population pharmacokinetics of phenobarbital, valproic acid and zonisamide. EPHX1 polymorphisms may be associated with the pharmacokinetics of carbamazepine and the risk of phenytoin-induced congenital malformations. Similarly, the UDP-glucuronosyltransferase 2B7 genotype may affect the pharmacokinetics of lamotrigine. Gluthatione S-transferase null genotypes are implicated in an increased risk of hepatotoxicity caused by carbamazepine and valproic acid. This article summarizes the state of research on the effects of mutations of drug-metabolizing enzymes on the pharmacokinetics and pharmacodynamics of AED therapies. Future directions for the dose-adjustment of AED are discussed.